Uma abordagem sistêmica no planejamento e monitoramento de atividades em cursos de graduação a distância - Costa Neto, Oswaldo Evaristo da (2015)
The distance learning in Brazil is a reality and, to each day, has increased the number of institutions, courses and people, who aspire to qualify professionally and even pursue an undergraduate or graduate degree. The accreditation of technical and higher education institutions to implement the modality of distance education; the creation of the Program Open University of Brazil – which allowed undergraduate and graduate degrees in various locations for partnership between public institution of higher education; and municipal management for the creation of an ODL center. These three main topics listed above, were determining factors for the growth in the number of students enrolled in distance education in Brazil. In this type of education, teachers and tutors are responsible for mediation of student learning, but for that to happen satisfactorily, it is essential the use technologies and methodologies that enable them to plan and monitor the activities assigned to students. The practice of teaching an undergraduate, as an open distance learning, has been a challenge for teachers of the curricular subjects - especially with regard to the activities assigned to students. Therefore, the present research work presents a methodology for a systematic approach in the planning and monitoring of activities in undergraduate distance learning courses.